Pengembangan Komik Digital dengan Mengintegrasikan Nilai-Nilai Keislaman sebagai Media Pembelajaran pada Materi Pokok Ruang Lingkup Biologi - Raneza, Felzia; Widowati, Hening; Santoso, Handoko (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2022)
The developments in education can be seen from various curriculum renewals and the quality of educators. To achieve the expected learning objectives, educators are also required to be able Â develop skills in making learning materials that will be used. The purpose of development research is to produce products in the form of Digital Comics by Integrating Islamic Values as Biology Learning Media in the Main Material of the Scope of Biology. Overcoming problems and meeting existing needs by being used as supporting facilities and infrastructure for the learning process and realizing national education goals. This digital comic development method uses the 4D model consisting of 4 stages, namely Define (defining), Design (design), Develop (development), and Desseminate (dissemination). Based on the results of the validation data analysis, the media aspect obtained a percentage of 85.2%, the validation results from the material aspect obtained a percentage of 90%, the validation results from the Islamic values aspect obtained a percentage of 94%, the validation results from subject teachers obtained a percentage of 91 .5%, and from the small group trial results obtained a percentage of 90.5% which includes media aspects, material aspects and Islamic values, Overall product assessment from expert validation and small group trials obtained an average of 90% with